Solving by substitution:
y = 4x - 3
2x + 7y = 41
Let us substitute the first equation y = 4x - 3 into the second.
2x + 7y = 41
2x + 7(y = 4x -3) = 41
2x + 7(4x -3) = 41
So that's the third option.
I hope this helps.
The equation of a elipse:
The length of the major axis is equal 2a if a > b or 2b if b > a.
We have
therefore the length of the major axis is equal 2 · 7 = 14.
Answer:
x=9
Step-by-step explanation:
We can use similar triangles and ratios. Put the small triangle side over the large triangle side.
9cm 3x -20
---------- = ---------------- We need to add the sides to get to the larger triangle
72+9 cm 3x-20 + 56
We can cross multiply to solve
9 * (3x-20+56) = (72+9) * (3x-20)
Simplify
9*(3x+36) = 81*(3x-20)
Distribute
27x +324 = 243x -1620
Subtract 27x from each side
27x-27x +324 = 243x-27x -1620
324 = 216x-1620
Add 1620 to each side
324+1620 = 216x
1944 = 216x
Divide each side by 216
1944/216 = 216x/216
9=x
Answer:
49
Step-by-step explanation:
substitute b = - 6 and c = 7 into the expression and evaluate
c - 7b = 7 - (7 × - 6) = 7 - (- 42) = 7 + 42 = 49
Answer:
is the number 4
so 13/16 3/16
Step-by-step explanation: